Analisis Kebutuhan Guru Penjas Dalam Pengembangan Kurikulum Berbasis Permainan Bola Basket - Syahruddin; Muh Syahrul Saleh; Muh Sahib Saleh (PT Mediatama Zayna Indonesia, 2025)
This study aims to analyze the needs of Physical Education, Sports, and Health (PJOK) teachers in developing a basketball-based curriculum at SMP Negeri 3 Makassar. The research method used is qualitative with a descriptive explorative approach. Data were collected through in-depth interviews, learning observations, and curriculum documentation studies and Lesson Implementation Plans (RPP). The results showed that 85% of PJOK teachers stated that the curriculum used had not optimally integrated basketball into the learning process. In addition, there were limitations in facilities and infrastructure by 75%, and 80% of teachers experienced minimal training related to educational game learning. Observations of the learning process also revealed the dominance of instructional methods that did not involve active student participation. Analysis of curriculum documents found no special RPP based on basketball games and learning objectives that emphasized basic cognitive and psychomotor aspects. This study recommends the development of an innovative basketball-based curriculum, increased training for teachers, and the provision of adequate media and learning facilities to improve the effectiveness of PJOK learning. The implementation of the curriculum is expected to improve learning motivation, basketball technical skills, and sportsmanship character of students at SMP Negeri 3 Makassar.